Efek Limitasi Konsumsi Garam dan Kopi pada Lansia Penderita Hipertensi - Joni Haryanto; Marini Marini (Universitas Airlangga, 2007)
Introduction: One of elderly’s problem in Health Center Karambitan II Tabanan Bali was hypertension. Elderly usually likes or has a habit consuming coffee and salty food everyday. This study was used a pre-experimental one group pre-post test design. The objective of this study was to analyze the effect of consumption limitation of coffee and salt on vital sign in elderly with hypertension. The subjects were elderly with hypertension which stay with their family who lived at Karambitan II Tabanan Bali Health Center region. Method: There were 28 samples which recruited by using total sampling who met to the inclusion criteria. Data were analyzed by using Wilcoxon Sign Rank Test, with significance level α≤0.05. Result: The result showed that there was an effect of consumption limitation of coffee and salt on systolic blood pressure (p=0.00000), diastolic blood pressure (p=0.00000) and heart rate (p=0.00000). Discussion: It can be concluded that there was an effect of consumption limitation of coffee and salt to decrease blood pressure and heart rate in elderly with hypertension who lived at Karambitan II Tabanan Bali Health Center regio. Community nurses should give health education for elderly in public health center periodically for reducing incidence of hypertension.